Analisis Bibliometrik : Penelitian Literasi Digital dan Hasil Belajar pada Database Scopus (2009-2023) - Septiany Maulani Soraya; Kurjono Kurjono; Ilham Muhammad (LP. Ma'arif Janggan Magetan, 2023)
High digital literacy skills can make it easier for students to follow every learning process. Learning outcomes are one indicator of successful learning in the academic field. The purpose of this research is to look at the research landscape related to digital literacy and learning outcomes from the Scopus database, the method used is bibliometric analysis. The results of the study show that the number of publications related to digital literacy and learning outcomes increases every year from 2018 to 2022. The largest number of documents is in the United States, the highest number of documents is in institutions or universities